2010
DOI: 10.5194/acp-10-4491-2010
|View full text |Cite
|
Sign up to set email alerts
|

Marine boundary layer over the subtropical southeast Pacific during VOCALS-REx – Part 1: Mean structure and diurnal cycle

Abstract: Abstract.Atmospheric subsidence over the subtropical southeast Pacific (SEP) leads to a low-level anticyclonic circulation, a cool sea surface and a cloud-topped marine boundary layer (MBL). Observations in this region from a major field campaign during October and November 2008, the VOCALS Regional Experiment, provide ample data to characterize the lower atmospheric features over the SEP. The observations are also useful to test the ability of an area-limited, high-resolution atmospheric model to simulate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
90
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 37 publications
13
90
0
Order By: Relevance
“…3b, yields a low bias in the ECMWF analysis. The correlation is lower (∼0.54) and the 1-sigma uncertainty is ∼70 m. The systematic low bias in ECMWF ABL height is consistent with previous weather and climate model studies over the region (e.g., Bretherton et al, 2004;Rahn and Garreaud, 2010;Wyant et al, 2010;von Engeln and Teixeira, 2011;Wang et al, 2011).…”
Section: Abl Height Comparisonssupporting
confidence: 71%
See 1 more Smart Citation
“…3b, yields a low bias in the ECMWF analysis. The correlation is lower (∼0.54) and the 1-sigma uncertainty is ∼70 m. The systematic low bias in ECMWF ABL height is consistent with previous weather and climate model studies over the region (e.g., Bretherton et al, 2004;Rahn and Garreaud, 2010;Wyant et al, 2010;von Engeln and Teixeira, 2011;Wang et al, 2011).…”
Section: Abl Height Comparisonssupporting
confidence: 71%
“…Such radiosonde ABL heights derived from MRG method are consistent with the ABL heights derived from the radiosonde inversion base from the same region (e.g., Fig. 4a of Rahn and Garreaud, 2010 and Fig. 10 of Wyant et al, 2010) as well as the cloud top height measurements from the airplane cloud radar during the VOCALS campaign (e.g., Fig.…”
Section: The Abl Structure Along the ∼20 • S Transectsupporting
confidence: 65%
“…Similarly to the subtropical region off the California coast, such conditions lead to a cold well-mixed boundary layer topped by a persistent stratocumulus deck (Rahn and Garreaud, 2010;Toniazzo et al, 2011). Due to a large area of coverage and persistence of stratocumulus clouds, this region significantly affects planetary albedo.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Rather, we look at the sensitivity of the Sc to lifting and lowering of the layer by a "kinematic gravity wave", the details of which are specified from observed GOES10 imagery, to examine the physics behind the clearing of the Sc. We point out that the gravity wave packets under consideration in this paper have a different source to the "upsidence" wave described by Garreaud and Muñoz (2004) and Rahn and Garreaud (2010), which is due to mechanical blocking by the Andes of the westerly flow above the boundary layer. Such effects have been investigated using LES by Jiang and Wang (2012) by applying upsidence-subsidence waves of time periods from 6 to 48 h, and it was found that, perhaps because of the relatively long wave period, precipitation is significant in the clearing of the cloud.…”
Section: P J Connolly Et Al: Gravity Waves and Stratocumulusmentioning
confidence: 99%
“…Large-scale divergence was specified to be 3 × 10 −6 s −1 , which is consistent with both QuikSCAT and WRF simulations for the period in question (Rahn and Garreaud, 2010) and helps to maintain the inversion.…”
Section: P J Connolly Et Al: Gravity Waves and Stratocumulusmentioning
confidence: 99%